Interpersonal violence in peacetime Malawi. Issue 1 (27th December 2018) - Maine, Rebecca G; Williams, Brittney; Kincaid, Jennifer A; Mulima, Gift; Varela, Carlos; Gallaher, Jared R; Reid, Trista D; Charles, Anthony G
Abstract : Background: The contribution of interpersonal violence (IPV) to trauma burden varies greatly by region. The high rates of IPV in sub-Saharan Africa are thought to relate in part to the high rates of collective violence. Malawi, a country with no history of internal collective violence, provides an excellent setting to evaluate whether collective violence drives the high rates of IPV in this region. Methods: This is a retrospective review of a prospective trauma registry from 2009 through 2016 at Kamuzu Central Hospital in Lilongwe, Malawi. Adult (>16 years) victims of IPV were compared with non-intentional trauma victims. Log binomial regression determined factors associated with increased risk of mortality for victims of IPV. Results: Of 72 488 trauma patients, 25 008 (34.5%) suffered IPV. Victims of IPV were more often male (80.2% vs. 74.8%; p<0.001), younger (median age: 28 years (IQR: 23–34) vs. 30 years (IQR: 24–39); p<0.001), and were more often admitted at night (47.4% vs. 31.9%; p<0.001). Of the IPV victims, 16.5% admitted alcohol use, compared with only 4.4% in other trauma victims (p<0.001). In regression modeling, compared with extremity injuries, head injuries (3.14, 2.24–4.39; p<0.001) and torso injuries (4.32, 2.98–6.27; p<0.001) had increased risk of mortality. Compared with other or unknown mechanisms, penetrating injuries also had increased risk of mortality (1.46, 95% CI 1.17 to 1.81, p=0.001). Alcohol use was associated with a lower risk of mortality (0.54, 95% CI 0.39 to 0.75; p<0.001). Discussion: Even in a sub-Saharan country that never experienced internal collective violence, IPV injury rates are high. Public health efforts to measure and address alcohol use, and studies to determine the role of "mob justice, " poverty, and intimate partner violence in IPV, in Malawi are needed. Level of evidence: Level III.